2008
DOI: 10.1007/s10545-008-0978-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in noncompliant adults with phenylketonuria after resumption of the diet

Abstract: Interpersonal differences exist between adult patients on relaxed diet, in some of whom quality of life often remains good, while others can suffer from severe emotional distress. Returning to diet increases quality of life in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 6 publications
4
54
1
2
Order By: Relevance
“…In a quality‐of‐life study among 53 adult patients in Poland who had stopped taking a restricted diet, 17% experienced severe distress, 28% moderate distress and 55% positive well‐being. Returning to a restricted diet increased their quality of life, but the high cost of low‐protein products and poor knowledge regarding a restricted diet contributed to their failure in maintaining the diet (Bik‐Multanowski et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a quality‐of‐life study among 53 adult patients in Poland who had stopped taking a restricted diet, 17% experienced severe distress, 28% moderate distress and 55% positive well‐being. Returning to a restricted diet increased their quality of life, but the high cost of low‐protein products and poor knowledge regarding a restricted diet contributed to their failure in maintaining the diet (Bik‐Multanowski et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
“…SamplePower’s sample size and power analysis technique utilize Cohen’s calculations for determining effect size and study power [19]. For this investigation, an effect size of 1.22 was calculated from an r 2 value of 0.55 found in a 2008 paper which showed association between diet related plasma Phe improvements and quality of life in PKU patients [13]. Thus, for this study, a minimum sample size of 18 was determined to be sufficient for a power of 0.8 with α = 0.05, and a maximum of 5 covariates in linear models.…”
Section: Methodsmentioning
confidence: 99%
“…Although the consequences are not as severe as during infancy and young childhood, this noncompliance has been shown to lead to neurological sequelae such as increased risk of mood disorders [5], attention deficits [6,7], impairments to executive functioning [8-10], school performance and achievement [11], and social difficulties [12], issues which can certainly impact QOL. Past studies have implicated both high plasma Phe concentrations as well as the strict medical diet in reduced quality of life (QOL) for patients with PKU [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…In another study, patients on a restricted diet reported higher scores of general life‐satisfaction than both an off‐diet patient group and a reference sample . Moreover, some data suggest that returning to a strict diet after discontinuation for at least 3 months can significantly improve the subjective well‐being of patients, according to evaluation with the Psychological General Well‐Being Index …”
Section: Quality Of Lifementioning
confidence: 97%